We Shall Not be Moved: Adult Learners’ Intransigent Attitudes about Group Projects - Judy K. Favor; Mark Harvey (Adult Education Research Conference, 2016)
This study explored the effectiveness of a structured group project planning process designed to improve accountability, communication, satisfaction, and attitudes about group projects with adult learners.
Keywords: adult learning; group projects; accelerated courses; online learning